Kajian Literatur: Internalisasi Nilai-nilai Tasawuf dalam Ajaran Tarekat - Ahmad Fathan Abidi (PALAPA, 2021)
The aim of this research is to conduct a theoretical study of the internalization of Sufism values that are applied to the teachings of the tarekat. This study uses an in-depth systematic literature focusing on looking at the concept of internalizing Sufism values applied in the tarekat. In this research process, there are several stages consisting of the literature collection process, literature selection, analysis, and finally combining all the analyzes into a unified whole. The results of this study indicate that the ability of the salik to accept, understand, and carry out the teachings of the tarekat given by the mursyid can be directly through the internalization of Sufism values. Sufism values can be implemented as a form of mental or mental development in the form of patience, tawakkal, sincerity, taubah, qona'ah, zuhud and others so that these values require serious training (riyadho) so that the form of application can be maximized. by experiencing it as a whole.